2017
DOI: 10.1007/s10549-017-4526-8
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between biomarkers of primary breast cancer and subsequent brain metastases: an international multicenter study

Abstract: The majority of breast cancer patients with BM in this series had primary HER2-enriched tumors, followed by those with a triple-negative profile. One out of 5 patients had a receptor discrepancy between the primary tumor and subsequent BM. Therefore, we advise receptor status assessment of BM in all breast cancer patients with available histology as it may have significant implications for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Taylor et al [26] found an increase in myocardial perfusion defects in the region supplied by the left anterior descending artery 6 months after it was irradiated. The data of Kaidar-Person et al [27] suggested that irradiation of the left ventricle can result in early post-RT perfusion defects and there appeared to be a strong dose/volume dependence to the risk. In our study, three techniques showed similar mean dose of left anterior descending artery (p > 0:05).…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al [26] found an increase in myocardial perfusion defects in the region supplied by the left anterior descending artery 6 months after it was irradiated. The data of Kaidar-Person et al [27] suggested that irradiation of the left ventricle can result in early post-RT perfusion defects and there appeared to be a strong dose/volume dependence to the risk. In our study, three techniques showed similar mean dose of left anterior descending artery (p > 0:05).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that 10%–26% of HER2‐negative primary breast cancers become HER2+ in a subsequent brain metastasis, whereas conversely, 13%–15% of HER2+ primary malignancies may become HER2 negative at sites of subsequent metastatic disease . A multi‐institutional analysis of 167 patients with breast cancer with paired primary and brain metastasis tissue available found that 19% of patients had discordance in estrogen receptor/progesterone receptor status or HER2 receptor status between the two sources of tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that 10%-26% of HER2-negative primary breast cancers become HER2+ in a subsequent brain metastasis, whereas conversely, 13%-15% of HER2+ primary malignancies may become HER2 negative at sites of subsequent metastatic disease [33,34]. A multi-institutional analysis of 167 patients with breast cancer with paired primary and brain metastasis HER2 Amplification in GI Cancer Brain Metastases tissue available found that 19% of patients had discordance in estrogen receptor/progesterone receptor status or HER2 receptor status between the two sources of tissue [35]. Although this evolution in HER2 status may seem unexpected given that oncogenic drivers are frequently thought of as necessary for tumor maintenance, several recent analyses have highlighted the dynamic nature of tumor biology between primary and metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, BCBM therapeutically-relevant subtypes are usually inferred from the IHC profiling of the primary tumor or extra-cranial metastatic tissues. However, significant discrepancies have been recently demonstrated in the expression levels of ER and HER2 and the mutational landscape of primary and matched BCBM 36-38 . Therefore, if clinically feasible, it is currently recommended to perform a histopathological evaluation of the metastatic lesions to confirm the therapeutic subtype by at least reassessing the expression of HR and HER2 35 .…”
Section: Discussionmentioning
confidence: 99%